Privacy and employment law - Craig, John DR (Oxford, 1999)
"This book examines in a rigorous and open-minded fashion, the emergence of policies on privacy in the modern employment context and the gradually developing legal response. Adopting a human rights perspective, the author demonstrates that several legal systems are now transposing human rights law from the public sphere into the employment relationship in order to protect the individual rights of job candidates and employees. The human right of privacy is one of the cornerstone rights recognised in the employment context, and is the focus of this book. The book deals with the law as it presently stands in the UK, France, the USA and Canada and includes a careful analysis of the potential impact of the Human Rights Act 1999. "